Efficiency measurement for airports - Holvad, Torben; Graham, Anne (Proceedings from the Annual Transport Conference at Aalborg University, 2000)
The paper has two aims. Firstly, it will undertake an empirical application for European and Australian airports in order to expand the information concerning the potential to use efficiency measurement techniques (such as Data Envelopment Analysis and Free Disposal Hull) within the airport sector to assess performance. The available information concerns 25 European airports and 12 Australian airports. Secondly, the empirical application will provide new information concerning the performance for these airports and in particular the extent to which there are efficiency variations. A major conclusion of the analysis is that given the specification of inputs and outputs, Australian airports appeared to achieve higher levels of efficiency than the European airports. The identified pattern suggests that a “continent” impact may exist accounting for the efficiency differences rather than merely being related to technical efficiency differences.